The arrival of Islam in Malawi - Mdoka, Abbas Saidi; Bahari, Che Amnah (American Research Institute for Policy Development, 2019)
This paper seeks to shed more light on the question of when and how Islam arrived in Malawi, who introduced it and what was the motive for its inauguration. The paper also attempts to make an inquiry into how Christian missionaries sitting aloof observed, processed, and responded to the growth and developments of Islam within Muslim communities in Malawi. It will also discuss the social, economic, and political implications on Muslims, due to their refusal to send children to missionary school on account of “Education for Christianity”. And how the church, carefully drafted contemptuous desolation for Muslims which were borne due to church’s noble ambition to Christianize the already religious Muslims instead of strengthening their membership to the heathen hordes who at the time outnumbered both Muslims and Christians all together. The research data were obtained through library study of books, journal, and articles on the history of both Islam and Christianity.